Implementasi Penggunaan LKPD Pencemaran Air Berbasis STEM dan Model Learning Cycle 6E Terhadap Kemampuan Literasi Sains - Donny Auliya Arrohman*; Ayu Latiefah Eka Wahyuni; Insih Wilujeng; Suyanta Suyanta (Universitas Syiah Kuala, 2022)
The scientific literacy ability of students in Indonesia, whether measured by PISA or by several Indonesian researchers, is known to be still in the low category. The purpose of this study was to determine the use of STEM-based Water Pollution LKPD and the 6E learning cycle model on scientific literacy skills. The type of research used is descriptive. The sampling technique used is purposive sampling with a total sample of 43 students from class VII-B SMP Ma'arif Karangawen Demak. Data collection techniques used observation, interviews, and scientific literacy tests. The instrument used consisted of an interview guide with the teacher, an observation sheet on the implementation of learning, a learning observation note sheet, and a scientific literacy test instrument with 13 questions. The data analysis technique used is validity test, reliability test, and analytical descriptive. The results obtained for the aspect of identifying scientific issues get an average value of 69,77 (good category), explaining natural phenomena scientifically 86,05 (Very Good), interpreting data and evidence scientifically 45,35 (quite good), integrating science in technology and society 56,98 (good), using scientific knowledge in solving problems 48,84 (good enough), and aspects of designing and evaluating scientific investigations 66,28 (good). The average value of scientific literacy as a whole gets 62,21 in the good category so that through the implementation of the STEM-based Water Pollution LKPD and the 6E learning cycle model, it gave good results for students' scientific literacy skills